Analysis of the Public Service System at the Anduonohu Lurah Office, Kendari City - Mumpuni, Ayuningtiyas Putri; Umar, Adria Yansah; Asraf, Asraf; Rahmatia, Rahmatia (PT. Riset Press International, 2023)
This article is the result of research and discussion which aims to identify and analyze the Public Service System at the Anduonohu Lurah Office, Kendari City. Located in Poasia District, Anduonohu Village, Kendari City, Southeast Sulawesi, this research used a qualitative method based on field studies to find sources and information directly. Semi-structured interviews were conducted with 5 informants representing several characteristics such as gender and age differences. The results of this study indicate that the Public Service System at the Anduonohu Village Office, Kendari City, is practically good. However, the results of this study also illustrate that there is still a need for development and improvement, especially in terms of implementing time in completing services and the friendliness of employees to the public as service users in the future. This research is important for academics to serve as a reference and as a theoretical framework for conducting evaluations in improving public service systems. For local governments, this research can also be used as a reflection for improvement in terms of the quality of the public service system.